Dino Buzzati Interpreter of Silvio Ceccato: Il grande ritratto and Its Debt to Cybernetics - Lima, Eleonora (Quaderni d'Italianistica, 2022)
This essay examines the impact of the studies conducted by cybernetician Silvio Ceccato on Buzzati’s novella Il grande ritratto (1959). While the link connecting Buzzati’s fictional rendition of an artificial intelligence (AI) in the novella and Ceccato’s theories have previously been established by the critics, this study explores in-depth and for the first time how truly knowledgeable and receptive the author was to the then new field of cybernetics. By cross-referencing Il grande ritratto against Ceccato’s work, and Buzzati’s own newspaper articles dedicated to it, this study demonstrates how the novella’s techno-scientific substratum is fundamental to understand why Buzzati chose to write the character of Numero Uno, the AI, the way he did. Indeed, the story departs from the traditional depiction of humanoid robots and anticipates some of the contemporary issues concerning AI, from the “black box problem” and autonomy in neural networks, to biases in data. The purpose of this essay is to situate Il grande ritratto within Buzzati’s well-informed curiosity for Ceccato’s theories, while also showing how the author’s engagement with cybernetics was not at all atypical, but rather in line with the enthusiastic interest for the field animating many Italian artists between the late 1950s and early 1960s.